Genre awareness of English language education students: An Indonesian context - Sari, Rima Andriani; Padmadewi, Ni Nyoman; Ratminingsih, Ni Made; Budasi, I Gede (Edelweiss Applied Science and Technology, 2025)
Genre refers to the type of literary work characterized by a particular style, form, or content. Language students are expected to have good genre awareness, or the understanding and recognition of text types, to be able to understand texts. This study aims to measure the genre awareness of the students in an English Language Education study program at a state university in Indonesia and identify the genres as well as the aspects they perceived as difficult. This research employed a descriptive design. The data were gathered by using a reading test measuring knowledge of 13 genres and a questionnaire. There were 96 students involved in the research. Data analysis was done descriptively. From the results of data analysis, the following conclusions were obtained: first, the genre awareness of the students was categorized into average for five text types (narrative, recount, spoof, explanatory, and procedure) and was categorized as poor and failed for the other text types; second, students perceived the genres which were the most difficult to identify are hortatory exposition and analytical exposition, and the aspects of the text are significant lexico-grammatical features and the generic structure. Lecturers are thus recommended to teach genres and address the factors perceived to hinder the students' understanding of texts.